Risk factors for postoperative cerebrospinal fluid leak and meningitis after expanded endoscopic endonasal surgery. Issue 1 (January 2015) - Ivan, Michael E.; Bryan Iorgulescu, J.; El-Sayed, Ivan; McDermott, Michael W.; Parsa, Andrew T.; Pletcher, Steven D.; Jahangiri, Arman; Wagner, Jeffrey; Aghi, Manish K.
Abstract Postoperative cerebrospinal fluid (CSF) leak is a serious complication of transsphenoidal surgery, which can lead to meningitis and often requires reparative surgery. We sought to identify preoperative risk factors for CSF leaks and meningitis. We reviewed 98 consecutive expanded endoscopic endonasal surgeries performed from 2008–2012 and analyzed preoperative comorbidities, intraoperative techniques, and postoperative care. Univariate and multivariate analyses were performed. The most common pathologies addressed included pituitary adenoma, Rathke cyst, chordoma, esthesioneuroblastoma, meningioma, nasopharyngeal carcinoma, and squamous cell carcinoma. There were 11 CSF leaks (11%) and 10 central nervous system (CNS) infections (10%). Univariate and multivariate analysis of preoperative risk factors showed that patients with non-ideal body mass index (BMI) were associated with higher rate of postoperative CSF leak and meningitis (both p < 0.01). Also, patients with increasing age were associated with increased CSF leak (p = 0.03) and the length of time a lumbar drain was used postoperatively was associated with infection in a univariate analysis. In addition, three of three endoscopic transsphenoidal surgeries combined with open cranial surgery had a postoperative CSF leak and CNS infection rate which was a considerably higher rate than for transsphenoidal surgeries alone or surgeries staged with open cases (p < 0.01 and p = 0.04, respectively) In this series of expanded endoscopic transsphenoidal surgeries, preoperative BMI remains the most important preoperative predictor for CSF leak and infection. Other risk factors include age, intraoperative CSF leak, lumbar drain duration, and cranial combined cases. Risks associated with complex surgical resections when combining open and endoscopic approaches could be minimized by staging these procedures.